(3GdeSFhdjI GdLfGFjI ddTNU GdeYfhji (B: s (3OQGSI ebGQfI (B/ s - (3GMeO eMeO bGFO ebHds; (3MSfjf UGdM YHjOs; (3eMehO fLjH MSfis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2005)
(3jDcO Yde GdGLJeGY GdSjGSj (B: (3Gf GdHTQjI YGTJ ai aLQ GdJGQjN (B: (3MjGI GJSeJ HGdYRdI hGdaQOjI hGdYOhGf ef LGfH GdGbhjGA (B: (3h JejR GdefGN GdGLJeGYi HHWT GdGbhjGA hNha GdVYaGA (B((3h jHOh Gf GLQGe GdGTNGU GdeYfhjI UhQI eJWhQI heVNeI ef Pdc(B) (3hdJMbjb GdSdGe h eG JaQVg GdZQGFR GdGfSGfjI ef JMbjb ebheGJ GdMjGI (B((3ajWYe ef LhY h jGef ef Nha(B) (3fTGJ GdOhdI h eMhQ GgOGa GdbGfhf hefTGg (B: (3cGf MaX GdGef hGdfXGehGbJVJ YdI hLhO GdOhdI (B: (3ai Gf JJaQY YfgG eDSSGJ h GLgRI (B: (3JJeJY HGdMjGI h HGdTNUjI h gcPG JLSOJ UhQI GdTNUjI ZjQ GdeQFjI HOGAI HGdOhdI h cGf JTNjU GdSdWI Ydi gjFGJ MGce Gh GejQ jJbeU TNUjI GdOhdI h jLSOgGKe HQRJ TNUjGJ GNQi (B: (3ai UhQI eDSSGJ OjfjI Gh efXeGJ GbdjejI Gh GbJUGOjI (B: (3JfGgV SdWI GdOhdI Gh JSYi Gdi eTGQcJgG ai HYV GdLhGfHs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2005s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B452-462s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdGTNGU GdeYfhjIs; (3GdZQGFR GdGfSGfjIs; (3Yde GdGLJeGY GdSjGSjs; (3GdaQV hGdGfLGRs; (3GdeSFhdjI GdLfGFjI ddTNU GdeYfhis; (3GdfOe GdGjLGHjs; (3GdZdW hGdLgd s; (3GdJQNjU GdGOGQjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs